カラフトケン ジロー ノ ボウケン ショケン - 雨宮, 淳三; アメミヤ, ジュンゾウ; AMEMIYA, Junzo (国立極地研究所, 1962)
P(論文) A Sakhalin-type dog named "JIRO" was one of the two dogs that survived for a year (Feb. 1958-Jan. 1959) whithout any help of man. He died at Syowa Base in July 1960. As a result of the pathological observation on this "JIRO", the following changes have been noticed. The macroscopic changes are: 1) splenic and hepatic atrophy, 2) gastric dilatation caused by hair balls (tricho-bzoar) and 3) enlargement of kidney that is considered as swelling. The microscopic examination of this sample has failed to get any noticeable results, as the sample was damaged due to post-mortem change and poor storage. departmental bulletin paper